2019
DOI: 10.1111/jop.12817
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal site and biopsy technique for the diagnosis of oral mucosal autoimmune blistering disease?

Abstract: Background The aim of this study was to determine which biopsy method produces the best diagnostic yield in patients presenting with autoimmune blistering diseases (AIBDs) of the oral mucosa. Methods This was a retrospective audit of patients who were biopsied at least once for a suspected AIBD of the oral mucosa. The type (incisional or punch) and site of biopsies were recorded in conjunction with case notes, electronic records and histopathological reports in order to calculate sensitivity, specificity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The characteristic histopathological picture shows subepithelial splitting, with a non‐specific mixed infiltrate consisting of lymphocytes, histiocytes, plasma cells, neutrophils and eosinophils. 7 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 However, less eosinophilic granulocytes than in bullous pemphigoid have been observed. 108 Epithelial changes reminiscent of lichen planus with acanthosis, hypergranulosis, as well as vacuolar degeneration with fibrosis and a band‐like infiltrate have also been described.…”
Section: Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic histopathological picture shows subepithelial splitting, with a non‐specific mixed infiltrate consisting of lymphocytes, histiocytes, plasma cells, neutrophils and eosinophils. 7 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 However, less eosinophilic granulocytes than in bullous pemphigoid have been observed. 108 Epithelial changes reminiscent of lichen planus with acanthosis, hypergranulosis, as well as vacuolar degeneration with fibrosis and a band‐like infiltrate have also been described.…”
Section: Histopathologymentioning
confidence: 99%
“…lichen planus, infectious diseases, pemphigus vulgaris and erythema multiforme. The characteristic histopathological picture shows subepithelial splitting, with a non‐specific mixed infiltrate consisting of lymphocytes, histiocytes, plasma cells, neutrophils and eosinophils 7,100–111 . However, less eosinophilic granulocytes than in bullous pemphigoid have been observed 108 .…”
Section: Histopathologymentioning
confidence: 99%
“…For lesions in the mouth, an oral punch biopsy offers a convenient and practical method of confirming oral diagnosis. A recent study concluded that punch biopsy was more sensitive than scalpel biopsy for suspected autoimmune bullous disease . The buccal mucosa can be exposed by everting the cheek, placing the thumb at the commissure and reflecting the corner of the mouth, applying external pressure on the cheek with the index finger to present the buccal mucosa …”
mentioning
confidence: 99%
“…They also emphasize the need for gentle dissection by tilting the n°15 blade, in a second step, parallel to the bone surface (Stab-and-Roll technique). to their protocole, the authors were able to obtain 51 contributive gingival biopsies out of the 52 performed except for 1 direct immunofluorescence out of 25 which could not be interpreted due to the absence of epithelium in the specimen, Gilvetti et al [20] also present satisfactory and predictive results when the biopsies are performed within the attached gingiva (61 biopsies) compared to those performed on other oral sites: oral mucosa, palate, lip, toungue (64 biopsies). In their study, 72% and 34.37% of the biopsies were performed using a punch technique on the keratinized gingiva and on the other oral sites, respectively; 38% of patients had an autoimmune bullous diseases and 36% a lichen planus or a lichenoid lesion.…”
Section: Discussionmentioning
confidence: 98%
“…So, we believe that this approach does not change our results although bias is always possible. We have chosen to establish the level of contribution of the gingival specimens to diagnosis instead of taking into account the specificity and sensitivity calculations of the biopsy, as it is done in some studies [17,20]. Indeed, the sensitivity and specificity of a diagnostic test allows to determine its ability to identify respectively sick people (true positives), and not sick people (true negatives).…”
Section: Discussionmentioning
confidence: 99%